Key drivers for adopting design-build in public construction projects: Malaysian perspective - Zheng, Ping Lee; Rahimi, A. Rahman; Doh, Shu Ing (Universiti Sains Malaysia, 2021)
Design-build (D-B) had been applied in many advanced countries because the delivery method improves construction project success. While several megaprojects in Malaysia have adopted D-B, it is still uncommon in the local construction industry. Therefore, understanding the key drivers that are affecting the acceptance or rejection of D-B is crucial. However, that information is lacking in the existing body of knowledge. Thus, this research addresses that issue by identifying the key drivers for adopting D-B in the Malaysian construction sector from the standpoint of the core project parties (e.g., project clients, consultants and contractors). Questionnaire survey data from 111 professionals with D-B experience were analysed using inferential statistics, including t-test and analysis of variance (ANOVA). The outcome shows that the key drivers for industry practitioner in Malaysia for adopting D-B are: (1) "Maximise the use of resources between project team members", (2) "Sharing of expertise (design and technical) with project team members", (3) "Well-organised project team structure", (4) "High success rate" and (5) "Dispute prevention during the construction stage". Also, there are no significant differences found in the drivers between different geographical regions and project parties. Based on the investigations, this study adds to the current assortment of information in capturing the key drivers and providing an in-depth understanding of the underlying components for adopting D-B in Malaysia. Researchers and industry practitioners can use the findings to enhance the level of D-B adoption strategical